The The Effect of Taxpayer Awareness, Tax Understanding, Tax Sanctions, and Risk Preferences on Land and Building Taxpayer Compliance - Aminatus Sholikah; Syaiful Syaiful (INNOVATION RESEARCH JOURNAL, 2022)
The background of this research is that there is a phenomenon of decreasing taxpayer compliance. This study aims to examine the effect of taxpayer awareness, tax understanding, tax sanctions, and risk preferences on land and building taxpayer compliance. This study uses quantitative methods. The population in this study amounted to 95, while the sampling used the Non Probability Sampling technique using saturated sampling. The reason is because the population size is relatively small. The sample studied by the researcher is 95 taxpayers. The analysis technique uses instrument testing, classical assumption test, and hypothesis testing. For test tools using the Statistical Package for the Social Sciences (SPSS). The results of this study indicate that taxpayer awareness has a positive and significant effect on taxpayer compliance, tax understanding has a positive and significant effect on taxpayer compliance, tax sanctions have a positive and significant effect on taxpayer compliance and risk preferences have a positive and significant effect on taxpayer compliance